ULTRASTRUCTURAL FEATURES OF CARDIOMYOCYTE CONTRACTILE APPARATUS IN RAT OFFSPRING HEARTS FOLLOWING MATERNAL CHRONIC ALCOHOL INTOXICATION - I.V. Tverdokhlib; D.G. Marchenko (Проблеми екології та медицини)
Background. The mechanisms underlying the development of the heart contractile apparatus and the distribution of myofibrils in cardiomyocytes following intrauterine ethanol intoxication continue to be a topic of significant debate. The aim of this paper is to determine the dynamics of postnatal changes in the ultrastructure of ventricular contractile cardiomyocytes in the rat heart after chronic alcoholization of the maternal organism. Methods. The study focused on the hearts of rat offspring from birth to adulthood. Transmission electron microscopy was utilized to examine the ultrastructure of cardiomyocytes in various zones of the ventricular myocardium. Results. It has been observed that prenatal alcohol exposure induces cardiomyocyte heteromorphism, characterized by varying degrees of damage throughout postnatal ontogenesis in rat offspring. Specifically, cells exhibiting critical signs of destruction in the myocardium of intramural and subepicardial zones of both ventricles aggregate into clusters surrounded by morphologically intact cardiomyocytes, while irreversibly damaged cells with subendocardial localization appear isolated. Following birth, there is a progressive accumulation of mitochondria exhibiting signs of limited functional activity. These polymorphic organelles, featuring a matrix of moderate or low electron density with sporadically developed cristae, primarily concentrate in paranuclear regions and are dispersed along the interstices of myofibril dissociation. Conclusion. Maternal chronic alcohol intoxication results in enduring harm to the contractile apparatus of ventricular cardiomyocytes in rat offspring. This damage manifests as sarcomere structure disorganization, myofibril fragmentation and misalignment, notable suppression of sarcomerogenesis, and reduced myofibril content, all closely linked to mitochondrial alterations.